Super bolide explosion in the upper atmosphere and possible implications for very low earth orbit satellites: a case study on May 25, 2023 - Pimenta, A. A.; Adebayo, O. M.; Wrasse, C. M.; de Jesus, R.; Santos, A. M.; Batista, P. P.; Andrioli, V. F.; Fagundes, P. R.; Kherani, E. A.; Savio, S. A.; Olajide, O. F. (Frontiers in Astronomy and Space Sciences, 2025)
This event is the first documented study in the Brazilian sector regarding a super bolide whose explosion was equivalent to 21 kilotons of TNT (∼8.83 × 1013J). The energy released by this event in the altitude range from 96 to 99 km in the upper atmosphere was equivalent to the atomic bomb detonated at an altitude of approximately 550 m over the Nagasaki city, Japan, during World War II. This observation was detected by all-sky images system with a filter in near infrared (NIR) band from 715 to 930 nm, operating at Cachoeira Paulista (22.7°S, 45°W) and lidar observations of the mesospheric sodium and potassium layers, operating at São José dos Campos (23.1°S, 45.9°W), both observatories in Brazil. The all-sky images system showed strong explosion in the mesosphere and a subsequent long-lived meteor train with more than 14 min through the NIR band. On the other hand, the lidar showed that the meteor explosion occurred in an altitude range from 96 to 99 km with the consequent sodium and potassium atoms enhancement on the background layers. Shortly after the fireball explosion, a digisonde operating at Cachoeira Paulista detected a sudden appearance of a sporadic-E layer. Using GNSS data, an analysis of the generation of infrasonic pressure waves excited during meteor explosion is presented. In addition, thermospheric neutral density values obtained with Swarm Satellite B prior to, during, and after 25 May 2023, showed a neutral density peak on 25 May 2023, at ∼ 12 UT, after the super bolide explosion (∼4.5 h later), and reached approximately 0.574 × 10−12 kg/m3, 15% above the average neutral density value prior to event. In this work we present and discuss several features related to this super bolide explosion in the upper atmosphere/ionosphere.